An enhanced TOPSIS-based framework for MCDM with uncertain weights: Application to e-waste recycling partner selection - Sandhya Priya Baral; Prashanta Kumar Parida; Diptirekha Sahoo (Results in Control and Optimization)
This article presents a unique TOPSIS-based framework to address the problem of interval number comparison in multi-criteria decision-making with unclear criterion weights. The method simplifies the sorting process by converting interval number matrices into two separate exact number matrices. Entropy weights are determined using a predetermined factor in order to improve the accuracy of decision-making. The choices are then carefully evaluated using the TOPSIS approach. A real-world application in choosing e-waste recycling partners (e-WRP) shows how successful the suggested process is. Additionally, comparative studies are carried out to confirm the results’ robustness and dependability, emphasizing the method’s usefulness in actual decision-making situations.